A successive multi-phase transitions in polycrystalline BaFe2As2: Emergence of C4 phase - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
We report magnetization and resistivity studies on polycrystalline BaFe2As2 prepared by solid-state reaction, in the temperature range of 5-350 K, upto the field of 9 T. Low-field susceptibility exhibits multi-phase transitions with two new magnetic phase transitions beside the well-known transition at T approximate to 140 K from paramagnetic/antiferromagnetic-tetragonal/orthorhombic transitions. The phase at T similar to 40 K is attributed to the phase transition from antiferromagnetic-orthorhombic (C2-phase) to antiferromagnetic-tetragonal phase (C4-phase), while the phase transition at higher temperatures remains unsolved. Making an analogy to the antiferromagnetic nanosized particles, we suggest that BaFe2As2 consists of smaller but similar nanosized clusters. We have analyzed the magnetization data using the modified Langevin function on the basis of thermally activated induced uncompensated spins (thermoinduced moments). The nanosized clustering in this compound is evidenced by the exchange bias and coercivity stemming from the exchange coupling interactions between weak ferromagnetic bulk magnetization in clusters and spin-glass-like phase interface layers surrounding the clusters. We also observe that annealing enhances the superconductivity, similar to the effect of pressure on the superconductivity. We find that an exponential term well describes the resistivity of this compound due to magnon-assisted interband electron-phonon scattering between the bands with d(xz) and d(yz) orbitals forming two-hole pockets around the zone center and one electron pocket around the zone corner. We have also obtained the Kadowaki-Woods ratio (A/gamma(2)(0) = .6.9 x 10(-5) mu Omega cm (K mol/mJ)(2)) and the Sommerfeld-Wilson ratio (R-w = 6) for BaFe2As2, both ratios are much larger than those (A/gamma(2)(0) = 1 x 10(-5) mu Omega cm (K mol/mJ)(2), R-w = 2) for Kondo lattice systems, indicating the existence of a weak ferromagnetic correlation between Fe moments. It appears that magnon-mediated pairing is responsible for superconductivity. Finally, we observe zero resistance at T = 5 K in amorphous BaFe2As2, which gives a new insight into the superconductivity under very high pressure.
Keywords: Bulk superconductivity; Kondo lattice systems; C4 phase; magnon-mediated pairing; HIGH-TEMPERATURE SUPERCONDUCTIVITY; ANOMALOUS MAGNETIC-PROPERTIES; FERMI-LIQUID BEHAVIOR; ELECTRICAL-RESISTIVITY; IRON PNICTIDES; NEMATIC ORDER; VORTICES; CURRENTS; DENSITY; WAVE